The IMF's Communication Strategy. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
The strategy proposed in this paper seeks to build understanding and support for the IMF's reform agenda as outlined in the IMF's Medium-Term Strategy, further integrate communications with operations, raise the impact of communication tools, and rebalance outreach efforts.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet